Jumlahan Langsung pada Ring - Syafruddin Side; Muhammad Abdy; Annisa Uniarti (Jurusan Matematika FMIPA UNM, 2021)
This research is literature study that aims to examine the basic consept of external direct sum of ring, internal direct sum of ring, and properties of direct sum of ring. The study starts from the definitioan of external direct sum and internal direct sum. The main literature used is a book written by B. Hartley and T.O. Hawkes (1970). The result obtained explain and elaborated on the definitons of external direct sum and internal direct sum of ring, theorems about properties of direct sum of ring that accommodate a theorem resulting from the representation of the properties of direct sum of S-Near Ring and direct sum of modules relating to external rirect sum and internal direct sum of ring.